أحكام تعاطي مخدر الاستروكس ومشتقاته وآثارها في الفقه الإسلامي - الراغب، مظهر أحمد عمر حسن (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2020)
في الحقيقة ومع انتشار مخدر الاستروكس ومشتقاته المعاصرة، والتوجسات التي تداهم المجتمع بأسره، وما طالعتنا به مواقع التواصل الاجتماعي فيسبوك ويوتيوب من مقاطع فيديوهات لمدمنين يتعاطون مخدر الاستروكس ثبت أنه من أخطر أنواع المخدرات المخلقة التي عرفتها البشرية، لذلك حرص الإسلام على المحافظة على النفس والعقل ليحمي الإنسان من نفسه ويحافظ على صحته وعقله وماله، ويحمي المجتمع من المدمنين لأنهم مصدر خطر على غيرهم من الناس. وعليه فنصوص الشريعة الإسلامية ومقاصدها فيها من الشمولية والمرونة ما يستوعب المستجدات والنوازل والقضايا الحادثة، ودور العلماء والمجتهدين النظر في هذه النوازل، ومنها مخدر الاستروكس، والذي تسبب في العديد من المخاطر التي أصابت المجتمع بأسره وما صاحب هذه المخاطر من أضرار صحية، ونفسية، واجتماعية، واقتصادية. وعليه فالشريعة الإسلامية لم تحرم الخمر لذاتها حتى يكون تحريمها أمراً تعبدياً لا يقاس عليها غيرها من المسكرات، ولكن كان تحريمها نتيجة للأضرار الكثيرة المترتبة على تناولها، لذا قرروا عقوبة متعاطيها وحرمة الاتِّجار بها واعتبروا تعاطيها من الكبائر التي يستحق مرتكبها المعاقبة في الدنيا والآخرة. والله –تعالى -ما شرع لعباده شيئاً إلا لأنه يحقق مصالحهم وينفعهم في دينهم ودنياهم، وما حرم عليهم شيئاً إلا لكون ضررهم فيه، وترتب على انتشار مخدر الاستروكس المعاصر العديد من المخاطر التي أصابت المجتمع بكافة فئاته واتجاهاته، بدءاً من الجهات الأمنية والمؤسسات الصحية، ومروراً بعلماء الاجتماع، وعلماء النفس، ووصولاً إلى رجال الدين وغيرهم من أجل تحريمه وعقاب متعاطيه والحدّ من انتشاره بين فئات المجتمع. ونوصي بإعداد مشروع قانون يجرم تعاطي وترويج مخدر الاستروكس كباقي العقاقير التقليدية التي تسبب الإدمان، وتضمينه في الجداول المعتمدة في المحاكم كمخدر ضمن المخدرات المحلية والدولية، والتنسيق بين قطاعات الدولة المعنية بهذا الشأن كلٍ فيما يخصه لمواجهة تعاطي مخدر الاستروكس من خلال الحملات التوعوية المرئية والمسموعة على مواقع التواصل الاجتماعي، وتفعيل البرامج والأنشطة الشبابية في النوادي ومراكز الشباب للحد من حالة العزلة والانفراد التي تسهل انتشار هذا المخدر.
In fact, with the spread of Strox and its contemporary derivatives, and the apprehensions that afflict the entire community, and the video clips of Facebook and YouTube video clips of addicts who abuse Astrox, it has been proven that it is one of the most dangerous types of synthetic drugs known to mankind. A person is protected from himself and maintains his health, mind and money, and protects society from addicts because they are a source of danger to other people. Accordingly, the texts of Islamic Sharia and their purposes in them of comprehensiveness and flexibility that accommodate developments, calamities, and the issues occurring, and the role of scholars and diligent people to consider these calamities, including the drug Strox, which has caused many risks that afflicted the entire community and the accompanying risks of health, psychological and social harm, And economical. Based on that, the Islamic Sharia did not forbid alcohol for its own sake, so that its prohibition was a devotional matter against which no other intoxicant could be compared, but its prohibition was a result of the many harms that result from consuming it, so they decided to punish those who abuse it and the prohibition of trading in it, and considered its consumption as a major sin that deserves punishment in this world and the hereafter. By God- Almighty- what has prescribed to His servants nothing except because it achieves their interests and benefits them in their religion and world, and forbids them anything except because their harm is in it, and the spread of contemporary Strox drug has resulted in many dangers that afflicted society in all its groups and directions, starting with the security authorities and health institutions, and passing through With sociologists, psychologists, and even clerics and others, in order to prohibit it, punish drug users, and limit its spread among groups of society. We recommend that a draft law be prepared criminalizing the abuse and promotion of Strox, like other traditional drugs that cause addiction, and its inclusion in the tables approved in the courts as a drug within the domestic and international drugs, and coordination between the relevant state sectors in this regard, each in their respective jurisdiction, to confront the abuse of Astrox through the visual and audio awareness campaigns on websites Social communication, and activating youth programs and activities in clubs and youth centers to reduce the state of isolation and isolation that facilitate the spread of this drug.
Keywords: تعاطي المخدرات -- مخدر الاستروكس -- الأحكام الشرعية -- الفقه الإسلامي